1999
DOI: 10.1046/j.1460-9568.1999.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of juvenile isolation and morphine treatment on social interactions and opioid receptors in adult rats: behavioural and autoradiographic studies

Abstract: The consequences of juvenile isolation and morphine treatment during the isolation period on (social) behaviour and mu-, delta- and kappa-opioid receptors in adulthood were investigated by using a social interaction test and in vitro autoradiography in rats. Juvenile isolation reduced social exploration in adults. Morphine treatment counteracted this reduction in isolated rats, but decreased social exploration in nonisolated rats. Self-grooming and nonsocial exploration were enhanced after juvenile isolation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 57 publications
2
25
1
Order By: Relevance
“…There have also been several studies reporting altered social behaviors in rodents exposed to social isolation during adolescence. Isolation rearing has consistently been found to increase aggressive behaviors in male rats; however the effect on non-aggressive behaviors has been less consistent with some studies showing a significant decrease in social interaction while others found a significant increase in social behaviors (Lukkes et al, 2009; Meng et al, 2010; Van den Berg et al, 1999; Zhao et al, 2009). One possible reason for the contrasting results may be due to the inconsistent period of time rats were socially isolated (2–8 weeks).…”
Section: Social Interactionmentioning
confidence: 88%
“…There have also been several studies reporting altered social behaviors in rodents exposed to social isolation during adolescence. Isolation rearing has consistently been found to increase aggressive behaviors in male rats; however the effect on non-aggressive behaviors has been less consistent with some studies showing a significant decrease in social interaction while others found a significant increase in social behaviors (Lukkes et al, 2009; Meng et al, 2010; Van den Berg et al, 1999; Zhao et al, 2009). One possible reason for the contrasting results may be due to the inconsistent period of time rats were socially isolated (2–8 weeks).…”
Section: Social Interactionmentioning
confidence: 88%
“…In contrast, rats in the present study were able to engage in unrestricted species-typical social behavior for 21 hr/day in the home cage, such as pinning, chasing, and rolling, as well complex behavioral sequences of deception and surprise attacks (Panksepp et al, 1984). These behaviors play a critical role in the development of normal social relationships in socially housed rats (Hol et al, 1999; Van den Berg et al, 1999; Von Frijtag et al, 2002), and likely play a modulatory role in social learning tasks in which responding depends on the degree of familiarity between the subjects (see, for example, Choleris et al, 1998; Galef et al, 1998; Kavaliers et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, administration of morphine enhances play behavior, while administration of the mu-opiate receptor antagonist naloxone, reduces rough and tumble play (Panksepp et al, 1985; Vanderschuren et al, 1995; Guard et al, 2002; Trezza and Vanderschuren, 2008). Moreover, when juveniles are socially isolated, thereby eliminating all experiences of play, both mu and kappa receptors are significantly up-regulation in several nuclei related to emotional regulation (Van den Berg et al, 1999b). Thus, the reduction in rough and tumble play behavior could be a symptom of a down-regulation of functional mu-opiate receptors in MOR-F1 males or conversely, their low levels of play could induce alterations in opiate receptors.…”
Section: Discussionmentioning
confidence: 99%